PENGARUH STRES KERJA DAN INSENTIF TERHADAP KINERJA KARYAWAN PADA PT ARISTA AUTO LESTARI MEDAN - Nur Kesuma; Manda Dwipayani Bhastary; Emma Novirsari (Jurnal Mahkota Bisnis (Makbis), 2022)
The researcher selected PT. Arista Auto Lestari Medan as the object of study due to a decline in employee performance within the company. Performance is the output of employees working within the company, which significantly impacts the company's ability to achieve its goals. The decline in employee performance is attributed to workload and work pressure, which cause employees to experience stress and depression in meeting the targets demanded by the company. Additionally, the lack of incentives for employees who nearly reach the targets set by the company leads to decreased morale, further contributing to the decline in employee performance. The research method used by the researcher is a quantitative approach, with the type of research being descriptive quantitative. The population consists of all 78 employees, and the sample includes the entire workforce. The results of the hypothesis testing indicate that work stress and incentives have a significant simultaneous and partial effect on employee performance, with a coefficient of determination value of 0.427, indicating that work stress and incentives affect employee performance by 42.70%. The remaining 57.30% is influenced by other factors not studied, such as leadership, physical work environment, and work discipline